2022
DOI: 10.1002/adma.202206345
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inverted Perovskite Solar Cells via Improved Sequential Deposition

Abstract: Inverted‐structure metal halide perovskite solar cells (PSCs) have attractive advantages like low‐temperature processability and outstanding device stability. The two‐step sequential deposition method shows the benefits of easy fabrication and decent performance repeatability. Nevertheless, it is still challenging to achieve high‐performance inverted PSCs with similar or equal power conversion efficiencies (PCEs) compared to the regular‐structure counterparts via this deposition method. Here, an improved two‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Moreover, the UV–vis absorption spectrum of the perovskite film on SnO 2 ‐FOA shows slightly stronger absorption in the wavelength between 400 and 750 nm compared with that of the perovskite film on the pristine SnO 2 (Figure S13, Supporting Information), which may contribute to higher short‐circuit density ( J SC ). [ 38 ] However, the absorption onset of both perovskite films is the same as that of the control film, indicating their similar optical bandgaps ( E g s). Thus, the SnO 2 ‐FOA treated substrate can modulate the crystal growth and orientation for the final perovskite film, without affecting the E g of active layer.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, the UV–vis absorption spectrum of the perovskite film on SnO 2 ‐FOA shows slightly stronger absorption in the wavelength between 400 and 750 nm compared with that of the perovskite film on the pristine SnO 2 (Figure S13, Supporting Information), which may contribute to higher short‐circuit density ( J SC ). [ 38 ] However, the absorption onset of both perovskite films is the same as that of the control film, indicating their similar optical bandgaps ( E g s). Thus, the SnO 2 ‐FOA treated substrate can modulate the crystal growth and orientation for the final perovskite film, without affecting the E g of active layer.…”
Section: Resultsmentioning
confidence: 96%
“…[39] Furthermore, the results from time-resolved photoluminescence (TRPL) measurements (Figure S14b, Supporting Information) revealed that the perovskite films on SnO 2 -FOA had a longer average carrier lifetime (830.5 ns) than that on SnO 2 (446.4 ns), which further demonstrated the reduced trap-assisted NRR of the perovskite films via the FOA treatment. [38,40,41] To gain deeper insights into the mechanism for the reduced NRR losses, the effect of FOA on the ETL and ETL/perovskite interface was studied. The XPS measurement was performed on the ETL surface for the SnO 2 and SnO 2 -FOA-based samples (Figure 4a-c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Recently, this method attracted renewed attention due to its successful application in the fabrication of mixed cation-based perovskites. 37,38 Despite the relative success of these two methods, the most common method for perovskite layer fabrication is the solvent-engineering approach. 39 This method is based on the one-step approach, since all of the perovskite precursors are still deposited in a single spin-coating step, but with the application of an antisolvent shortly before the spin-coating is completed.…”
Section: Oscar Telschowmentioning
confidence: 99%
“…2,3 Among them, the p-i-n PSCs (inverted PSCs) have received wide attention because of their various advantages, such as low-temperature solution processing capacity and low hysteresis effect. [4][5][6] Meanwhile, the p-i-n PSCs also cater to the flexible devices and tandem devices.…”
mentioning
confidence: 99%